Unexpected record of pygmy white-toothed shrew Suncus etruscus in Central Slovenia (Insectivora, Mammalia) - Kryštufek, Boris (Annales. Series historia naturalis, 1997)
A single Suncus etruscus skull was found in an Asio otus pellet in Ljubljansko barje wetland, central Slovenia. The record is 60 km to the east of the actual range of Suncus etruscus. Since the pellet originates from the breeding season and includes also theree Microtus arvalis skulls, it is unlikely to be of a migratory owl.
Keywords: favna; Slovenia; Slovenija; sove